2009
DOI: 10.1016/j.coph.2009.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Current and potential inflammation targeted therapies in head and neck cancer

Abstract: Inflammation often exists in the tumor microenvironment and is induced by inflammatory mediators (cytokines, chemokines, and growth factors) produced by the tumor, stroma, and infiltrating cells. These factors modulate tissue remodeling and angiogenesis and actively promote tumor cell survival and chemoresistance through autocrine and paracrine mechanisms. Head and neck squamous cell carcinomas (HNSCCs) are highly inflammatory and aggressive in nature, and they express a number of cytokines and growth factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 48 publications
1
77
0
5
Order By: Relevance
“…Squamous cell head and neck carcinomas are highly inflammatory in nature and express a number of cytokines and growth factors involved in inflammation (47). Specifically, pretreatment serum IL6 levels have been found to predict recurrence and poor survival in head and neck cancer (48); smoking is associated with high IL6 levels, and this may result from the adverse effects of smoking on sleep patterns (49).…”
Section: Other Potential Mechanismsmentioning
confidence: 99%
“…Squamous cell head and neck carcinomas are highly inflammatory in nature and express a number of cytokines and growth factors involved in inflammation (47). Specifically, pretreatment serum IL6 levels have been found to predict recurrence and poor survival in head and neck cancer (48); smoking is associated with high IL6 levels, and this may result from the adverse effects of smoking on sleep patterns (49).…”
Section: Other Potential Mechanismsmentioning
confidence: 99%
“…Several immunomodulatory molecules are also regulated by the JAK/STAT cascade. Specifically, reduced Th1-dominated antitumor response on aberrant STAT3 activation contributes to cancer cell survival and proliferation, suggesting the role of STAT3 in the maintenance of the tumor microenvironment by contributing to the process of inflammation and angiogenesis (77,(80)(81)(82).…”
Section: Jak/stat Signaling In Gastric Tumorigenesismentioning
confidence: 99%
“…Several dysregulated proinflammatory signaling cascades including NF-kB, STAT3, and serine/threonine protein kinase B (AKT) have been linked to the carcinogenesis of HNSCC and play a pivotal role in the growth, proliferation, and survival of the head and neck cancer (6)(7)(8)(9)(10). For example, Sen and colleagues recently reported that STAT3 activation can even contribute to EGF receptor inhibitor resistance in HNSCC and thereby targeting of STAT3 may represent an effective treatment strategy (10).…”
Section: Introductionmentioning
confidence: 99%